Fetal complications associated with GDM: a matter to worry? - Singh, Priyanka; Somani, Pranita (International Journal Of Community Medicine And Public Health, 2022)
Background: The consequences of GDM to the fetus are more serious than those to mother. Amongst fetal effects, incidence of fetal macrosomia is increased in women with GDM and DM type 2. Study was conducted to study prevalence of gestational diabetes mellitus using diabetes in pregnancy study group India (DIPSI) criteria in our hospital and to study fetal outcome in pregnancy with Gestational diabetes mellitus. Methods: Case control study was conducted on 500 females between 24-28 weeks of pregnancy. 31 (6.2%) were diagnosed as gestational diabetes mellitus (GDM). 31 other pregnant females between 24-28 not having diabetes were taken in control group. Follow up of all pregnant females was done. Babies were evaluated for any gross anomaly, birthweight of babies were taken, APGAR score was noted. Results: Maximum females (38.7%) with GDM were in age group of 25-29 years. Mean Basal Metabolic Index in GDM was 26.74 while in NGDM it was 22.48. Perinatal loss in GDM was 90.3%. Post-partum haemorrhage was seen in 9.7%. Intrauterine growth retardation (IUGR) in GDM was seen in 12.9%. Macrosomia was seen in 16.1%, preterm delivery in 9.7%, APGAR score <7 at 5 min in 6.5%, birth injury in 3.2%GDM. Mean weight in GDM was seen in 2.944 kgs and NGDM in 2.726 kgs. Conclusions: Postpartum screening should be at regular interval to detect recurrence of future diabetes. With effective screening and management of GDM, from “diabetes capital of the world,” we (INDIA) can lay claim to be “diabetes care capital of world.”